Comparative study between ligation and excision versus ligation only in surgical treatment of hemorrhoid (pain, bleeding, stricture) in Mosul Teaching Center - Jawad, Nisreen Khalid; Al-Gailani, Ali Jummaah Ali; Ayoob, Raad Abdallhadi (Scientific Journal of Medical Research, 2024)
Aim: This study aims to compare excision and ligation versus ligation only in the management of hemorrhoids in terms of pain, bleeding, and stricture. Methods: This study consisted of 100 patients (aged 18-70 years) who were treated at Al-Mosul Teaching Center from January 2021 to December 2022. A total of 50 patients were operated by using ligation and excision (group 1) and 50 patients by using ligation only, both methods for grade II or III hemorrhoids. The mean age was 44 years (18–75 years). The procedures were performed under GA or spinal anesthesia in a short-stay surgery unit. The pain, bleeding, and stricture after 3-6 months were recorded. Results: among 100 patients, 50 patients treated with ligation and excision complained of 70% of patient with bleeding post-operation and 28% had severe pain while the other group treated with ligation complained of 24% with bleeding post-operation and 10 % with severe pain. Conclusion: Suture ligation of hemorrhoids is an easy-to-perform technique and had good results for hemorrhoids, effective with less postoperative pain and blood loss.